Cultural identity and citizenship with the challenges of globalization - Alshamsi, Huda (Journal of Humanities & Social Sciences, 2022)
Citizenship, as that emotional feeling that is based on three important pillars, including democracy in human rights and civil society and the relationship of citizenship to identity is the role of the individual in the active participation in the social construction of human societies, globalization in citizenship affects if there are members of society as individuals and groups as well as possible That the individual and social affiliations through the group of anthropological features that characterize social groups within society affect citizenship, and thus there can be a specific relationship between globalization and cultural or religious identity or other identity patterns, and globalization today threatens identity and citizenship on Both . Since societies belonged to the system of globalization according to these global changes that forced societies to interact with globalization. Societies must be remedied this issue to preserve their identity and the affiliation of individuals to it, whether as a geographical or social dimension, and here the problem of research is formed in discussing the dimensions of citizenship, identity, globalization and the relationship between them and stands on the most important challenges facing societies. We note that culture and citizenship are formed with the challenges of globalization as a mixture of directions for peoples, and therefore it changes the characteristics and identity of these peoples, so we must mention them. The country must develop long -term plans for the challenges of globalization, and thus began to suit peoples in their stability, and also weakens all the difficulties facing these peoples to preserve their identity and culture because of a great impact on those societies.